Polyene Phosphatidylcholine Ameliorates High Fat Diet-Induced Non-alcoholic Fatty Liver Disease via Remodeling Metabolism and Inflammation - Lu, Yang; Feng, Tingting; Zhao, Jinxiu; Jiang, Pengfei; Xu, Daxiang; Zhou, Menglu; Dai, Mengyu; Wu, Jiacheng; Sun, Fenfen; Yang, Xiaoying; Lin, Qisi; Pan, Wei (Frontiers in Physiology, 2022)
Recent years have witnessed a rise in the morbidity of nonalcoholic fatty liver disease (NAFLD), in line with the global outbreak of obesity. However, effective intervention strategy against NAFLD is still unavailable. The present study seeks to elucidate the effect and mechanism of polyene phosphatidylcholine (PPC), a classic hepatoprotective drug, on NAFLD induced by high fat diet (HFD). We found that PPC intervention lowered the body weight, reduced the mass of liver, subcutaneous, epididymal and brown fats in HFD mice. Furthermore, PPC supplementation significantly mitigated liver steatosis, and improved glucose tolerance and insulin sensitivity in HFD mice, which was accompanied by a declined serum level of triglyceride, low density lipoprotein, aspartate aminotransferase and alanine aminotransferase. Using transcriptome analysis, there were 1789 differentially expressed genes (|fold change| ≥ 2, P < 0.05) including 893 upregulated genes and 896 downregulated genes in the HFD group compared to LC group. 1114 upregulated genes and 1337 downregulated genes in HFD+PPC group were identified in comparison to HFD group. With the help of Gene Ontology analysis, several dysregulated biological processes including “lipid metabolic process (GO: 0006629)”, “lipid modification (GO: 0030258)” and “lipid homeostasis (GO: 0055088)” may play key roles in hepatic lipid metabolism. Though Kyoto Encyclopedia of Genes and Genomes pathway analysis, we found pathways associated with hepatic metabolism homeostasis and inflammation. Among them, the dysregulated pathway “Non-alcoholic fatty liver disease (mmu04932)” (P value = 0.00698) inspired the potential mechanism of PPC to ameliorate NAFLD and deserves further study. The study also found that lipolysis, fatty acid oxidation and lipid export associated genes were upregulated while the genes in uptake of lipids and cholesterol synthesis were downregulated in the liver of HFD mice after PPC supplementation. Interestingly, PPC attenuated the metabolic inflammation via inhibiting M1 macrophage polarization in the livers of mice fed by HFD. In summary, this study demonstrates that PPC can ameliorate HFD-induced liver steatosis via reprogramming metabolic and inflammatory processes, which inspired clues for further clarifying the intervention mechanism of PPC against NAFLD.